The role of the business competition supervisory commission in response to allegations of predatory pricing practices in e-commerce - Komaria Nur Aulia AP (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
The presence of E-Commerce provides various conveniences, one of which is the ease of exporting and importing goods, as E-Commerce is a trade that has no geographical boundaries. However, because of this, there are allegations of predatory pricing practices in E-Commerce that have caught the attention of the government, as they can cause losses for other businesses and consumers. The allegations involve the discovery of imported products being sold at much lower prices than local products. Nevertheless, not all actions can be considered as prohibited predatory pricing practices, there is a need for advidence or assessment to be conducted by the Business Competition Supervisory Commission (KPPU). This study utilizes normative juridical research. The result of this study is that preatory pricing practices are prohibited under Article 20 of Law Number 5 of 1999 concerning the Prohibition of  Monopolistic Practices and Unfair Business Competition, where a matter can be considered a prohibited predatory pricing practice if it fulfills the elements stated in Article 20. In the case of allegations of predatory pricing practices in E-Commerce, The KPPU can also impose administrative sanctions on businesses proven to engage in prohibited predatory pricing practices under competition law.